Manufacturing Road Map for Tissue Engineering and Regenerative Medicine Technologies. (9th January 2015) - Hunsberger, Joshua; Harrysson, Ola; Shirwaiker, Rohan; Starly, Binil; Wysk, Richard; Cohen, Paul; Allickson, Julie; Yoo, James; Atala, Anthony
Abstract : The 2014 Regenerative Medicine Foundation Annual Conference had a vision of assisting with translating tissue engineering and regenerative medicine-based technologies by assembling leaders in the field to cover critical areas, including regulatory pathways for regenerative medicine therapies, strategic partnerships, resource coordination, developing standards, government support, industry priorities, biobanking, and new technologies. This article covers lessons learned from the manufacturing sessions and early survey results and provides a road map for future developments in the field. Abstract: Summary: The Regenerative Medicine Foundation Annual Conference held on May 6 and 7, 2014, had a vision of assisting with translating tissue engineering and regenerative medicine (TERM)-based technologies closer to the clinic. This vision was achieved by assembling leaders in the field to cover critical areas. Some of these critical areas included regulatory pathways for regenerative medicine therapies, strategic partnerships, coordination of resources, developing standards for the field, government support, priorities for industry, biobanking, and new technologies. The final day of this conference featured focused sessions on manufacturing, during which expert speakers were invited from industry, government, and academia. The speakers identified and accessed roadblocks plaguing the field where improvements in advanced manufacturing offered many solutions. The manufacturing sessions included (a) product development toward commercialization in regenerative medicine, (b) process challenges to scale up manufacturing in regenerative medicine, and (c) infrastructure needs for manufacturing in regenerative medicine. Subsequent to this, industry was invited to participate in a survey to further elucidate the challenges to translation and scale-up. This perspective article will cover the lessons learned from these manufacturing sessions and early results from the survey. We also outline a road map for developing the manufacturing infrastructure, resources, standards, capabilities, education, training, and workforce development to realize the promise of TERM.